Registers of Communication - Agha, Asif; Frog (Studia Fennica Linguistica, 2015)
In any society, communicative activities are organized into models of conduct that differentiate specific social practices from each other and enable people to communicate with each other in ways distinctive to those practices. The articles in this volume investigate a series of locale-specific models of communicative conduct, or registers of communication, through which persons organize their participation in varied social practices, including practices of politics, religion, schooling, migration, trade, media, verbal art, and ceremonial ritual. Drawing on research traditions on both sides of the Atlantic, the authors of these articles bring together insights from a variety of scholarly disciplines, including linguistics, anthropology, folklore, literary studies, and philology. They describe register models associated with a great many forms of interpersonal behavior, and, through their own multi-year and multi-disciplinary collaborative efforts, bring register phenomena into focus as features of social life in the lived experience of people in societies around the world.